Apoyo a la secretaria de Planeación Municipal de Paz de Río en la revisión y supervisión de proyectos de infraestructura en ejecución como auxiliar de Ingeniería Civil (2022)
The following document is presented as a report of the degree project) in the internship modality at the Civil Engineering program of the Antonio Nariño University, which has the purpose of supporting the Municipal Planning Secretary of Paz de Río (Boyacá), at the review and supervision of civil projects developed, based on the different approved designs and their annexes, as a Civil Engineering assistant; participating in activities such as the preparation, updating and/or revision of the technical specifications and budgets on the different projects taking into account the value, time and the timely completion of the same, reports developments, land use certificates, nomenclature and variables taking into account the Land Management Scheme (EOT) of Paz de Rio town; As well as the accompaniment and supervision at the technical visits in reference to the projects that were carried out at the town during the development of the internship, among others, in addition to those referred on the log book activities, kept by a photographic record with the purpose of demonstrating the activities carried out during the internship.